2004
DOI: 10.1111/j.1600-0781.2004.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiologic characterization of photosensitivity in HIV‐positive individuals

Abstract: Photosensitivity associated with HIV infection is an increasingly recognized dermatologic condition with a heterogeneous clinical presentation. AA ethnicity and HAART were independent indicators for the diagnosis of photosensitivity, whereas CD4+ and UV exposure had non-significant associations. The subtleties in these and other clinical variables may directly aid in the recognition and diagnosis of this poorly characterized disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 22 publications
1
37
1
7
Order By: Relevance
“…Although certain antiretrovirals, such as saquinivir, possess photosensitizing properties, we previously demonstrated that this increase in photosensitivity is not likely due to this or any other medication. 23 Lastly, similar to previous reports, molluscum contagiosum was also significantly increased with HAART use (5.8% vs 2.6%; P = .03). 28,39,40 While disseminated molluscum contagiosum is often noted in severely immunocompromised patients, the authors believe this increased incidence among HAART users may be a result of the immunologic recovery syndrome where previously unidentified viral antigens are recognized after treatment initiation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although certain antiretrovirals, such as saquinivir, possess photosensitizing properties, we previously demonstrated that this increase in photosensitivity is not likely due to this or any other medication. 23 Lastly, similar to previous reports, molluscum contagiosum was also significantly increased with HAART use (5.8% vs 2.6%; P = .03). 28,39,40 While disseminated molluscum contagiosum is often noted in severely immunocompromised patients, the authors believe this increased incidence among HAART users may be a result of the immunologic recovery syndrome where previously unidentified viral antigens are recognized after treatment initiation.…”
Section: Discussionsupporting
confidence: 87%
“…19 We have also previously reported an increase in the prevalence of photosensitivity with HAART use. 23 The specialized dermatology clinic where this study was conducted treats HIV-infected individuals who are mainly from the inner city area of east Baltimore, Maryland. The majority of the subjects are African American (69%), which is indicative of the overall east Baltimore demographic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former may require corticosteroid therapy alone whereas the latter may also require treatment with an antimicrobial agent. Other inflammatory diseases occurring after ART that are less well-established include photodermatitis [47].…”
Section: Acquisition or Exacerbation Of Nonautoimmune Inflammatory DImentioning
confidence: 99%
“…New photosensitizers are reported as a cause of skin disease, whereas others are used for phtnototherapy. Studies are still being undertaken on the mechanisms and chromophores, responsible for diseases associated with photosensitivity, such as HIV infection [6,7].…”
Section: Introductionmentioning
confidence: 99%